Forest owner motivations and attitudes towards supplying biomass for energy in Europe - Blennow, Kristina (2017)
The European Commission expects the use of biomass for energy in the EU to increase significantly between 2010 and 2020 to meet a legally binding target to cover at least 20% of EU’s total energy use from renewable sources in 2020. According to estimates made by the member states of the EU, the direct supply of biomass from forests is expected to increase by 45% on a volume basis between 2006 and 2020 in response to increasing demand (Beurskens LWM, Hekkenberg M, Vethman P. Renewable energy projections as published in the national renewable energy action plans of the European Member states. ECN and EEA; 2011. http://https://www.ecn.nl/docs/library/report/2010/e10069.pdf [accessed 25.04.2014]; Dees M, Yousef A, Ermert J. Analysis of the quantitative tables of the national renewable energy action plans prepared by the 27 European Union Member States in 2010. BEE working paper D7.2. Biomass Energy Europe project. FELIS e Department of Remote Sensing and landscape information Systems, University of Freiburg, Germany; 2011). Our aims were to test the hypotheses that European private forest owners’ attitudes towards supplying woody biomass for energy (1) can be explained by their responses to changes in prices and markets and (2) are positive so that the forest biomass share of the EU 2020 renewable energy target can be met. Based on survey data collected in 2010 from 800 private forest owners in Sweden, Germany and Portugal our results show that the respondents’ attitudes towards supplying woody biomass for energy cannot be explained as direct responses to changes in prices and markets. Our results, furthermore, imply that European private forest owners cannot be expected to supply the requested amounts of woody biomass for energy to meet the forest biomass share of the EU 2020 renewable energy target, at least if stemwood is to play the important role as studies by Verkerk PJ, Anttila P, Eggers J, Lindner M, Asikainen A. The realisable potential supply of woody biomass fromforests in the European Union. For Ecol Manag 2011;261: 2007e2015, UNECE and FAO. The European forest sector outlook study II